2020
DOI: 10.1158/1078-0432.ccr-19-1373
|View full text |Cite
|
Sign up to set email alerts
|

Deubiquitinase Activity Profiling Identifies UCHL1 as a Candidate Oncoprotein That Promotes TGFβ-Induced Breast Cancer Metastasis

Abstract: Purpose: Therapies directed to specific molecular targets are still unmet for patients with triple-negative breast cancer (TNBC). Deubiquitinases (DUB) are emerging drug targets. The identification of highly active DUBs in TNBC may lead to novel therapies. Experimental Design: Using DUB activity probes, we profiled global DUB activities in 52 breast cancer cell lines and 52 patients' tumor tissues. To validate our findings in vivo, we employed both zebrafish and murine breast cancer xenograft models. Cellular … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
113
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 40 publications
3
113
0
Order By: Relevance
“…Finally, we show that selective UCHL1 inhibitors can suppress fibrotic phenotypes in IPF cellular models without substantial cytotoxicity. While the precise role of UCHL1 in fibrosis remains to be determined, UCHL1 was recently identified as a potential target in triple-negative breast cancer (TNBC), where it promotes TGF-β1 signaling 8 and suppresses estrogen receptor expression. 30 1 and 2 represent powerful and selective probes to explore UCHL1 activity with potential application to substrate identification, mode of action studies, and cellular target profiling, which can accelerate future development of UCHL1 inhibitors as potential therapeutics.…”
mentioning
confidence: 99%
“…Finally, we show that selective UCHL1 inhibitors can suppress fibrotic phenotypes in IPF cellular models without substantial cytotoxicity. While the precise role of UCHL1 in fibrosis remains to be determined, UCHL1 was recently identified as a potential target in triple-negative breast cancer (TNBC), where it promotes TGF-β1 signaling 8 and suppresses estrogen receptor expression. 30 1 and 2 represent powerful and selective probes to explore UCHL1 activity with potential application to substrate identification, mode of action studies, and cellular target profiling, which can accelerate future development of UCHL1 inhibitors as potential therapeutics.…”
mentioning
confidence: 99%
“…Jin et al [50] reported that the miR-548e-5p, together with UBE-2C and zinc finger E-box binding homeobox (ZEB1/2), acts as a potential diagnostic biomarker and target for NSCLC. Moreover, another ubiquitin-protein UCHL1 was reported to promote uterine serous cancer cell proliferation, cell cycle progression [51], and TGFβ-induced breast cancer metastasis [52]. So far, no study has mentioned the relationship between miR-1246 and UBE-2C and UCHL1 in LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, we recently showed that 6RK73 decreases UCHL1 activity and thereby inhibits TGFβ/SMAD2 and SMAD3 signaling and breast cancer migration and extravasation. 48 We are convinced that the here reported strategy of small-molecule cyanimide-based probes can be expanded to other cysteine proteases and specifically DUBs. With the rising importance of the Ub system as source of practical drug targets we believe that these ABP tools will fill an unmet need allowing us to study active DUBs in their native environment in live cells or animals and as such aid in the development of future therapeutics that target diseases associated with ubiquitination.…”
Section: Discussionmentioning
confidence: 75%